A drive for better air service: How air service imbalances across neighboring regions integrate air and highway demands. (August 2018) - Ryerson, Megan S.; Kim, Amy M.
Abstract: Between 2000 and 2010, newly merged U.S. airlines decreased service to airports in small and mid-sized metropolitan regions, opting to consolidate their operations at high-value airport hubs (passenger transfer points). At this point travelers living in small and mid-sized regions likely began leaking, or abandoning their local airport to take flights from hub airports offering more convenient flight options. The extent of this practice, however, is not well established. Our study asks to what extent airline consolidation deepened the divide in service levels between airports that are 100–300 miles apart, and seeks to estimate the magnitude of air traveler leakage at small and medium airports across the U.S. We estimate that travelers living in small and mid-sized metropolitan regions have the incentive to "leak" from their airport to a distant, better-served airport. Our estimates suggest that 15.7%–31.8% of the total passengers living proximate to a small or mid-sized airport have the incentive to leak. Our estimates range from 10.8% to 33.0% for travelers facing a non-stop itinerary from their local airport and 33.3%–85.1% for travelers facing a connecting itinerary. The potential leaked passengers contribute 1–2.75% of average daily highway traffic at heavily congested portions of the interstate highways connecting airports and up to 10–12% of traffic on low density portions of the highway. Our study illustrates the relationship between interregional surface transportation and the aviation system by estimating the number of travelers who may choose to travel long distances by car to access a relatively busier, larger airport with better service. The results of this study help to shape the evolving role of airport managers in controlling demand and delay at major hub airports and in building and managing air service and smaller airports across the U.S.